2021
DOI: 10.2147/ndt.s314874
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concomitant Benzodiazepine Use on Efficacy and Safety of Esketamine Nasal Spray in Patients with Major Depressive Disorder and Acute Suicidal Ideation or Behavior: Pooled Randomized, Controlled Trials

Abstract: The impact of benzodiazepines on the efficacy and safety of esketamine as a rapid-acting antidepressant remains unclear. Materials and Methods: Data from two identically designed, randomized double-blind studies were pooled and analyzed on a post-hoc basis. In both studies, adults with major depressive disorder with acute suicidal ideation or behavior were randomized to placebo or esketamine 84 mg nasal spray twice-weekly for 4 weeks, each with comprehensive standard-ofcare (initial hospitalization and newly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…However, the concomitant use of benzodiazepines increased the risk of developing severe neurological AEs (χ2 = 4.10, p = 0.043). This finding is consistent with those of previous studies, which suggested that concomitant esketamine use with central nervous system depressants (e.g., benzodiazepines, opioids, alcohol) may worsen sedation (U.S. Food and Drug Administration, 2019; Diekamp et al, 2021). Given the frequent need for coprescriptions of hypnotics with esketamine, we recommend that non-benzodiazepines (e.g., zolpidem, zopiclone, zaleplon and eszopiclone) should be administered to mitigate the risk of severe neurological events.…”
Section: Serious Versus Non-serious Reportssupporting
confidence: 93%
“…However, the concomitant use of benzodiazepines increased the risk of developing severe neurological AEs (χ2 = 4.10, p = 0.043). This finding is consistent with those of previous studies, which suggested that concomitant esketamine use with central nervous system depressants (e.g., benzodiazepines, opioids, alcohol) may worsen sedation (U.S. Food and Drug Administration, 2019; Diekamp et al, 2021). Given the frequent need for coprescriptions of hypnotics with esketamine, we recommend that non-benzodiazepines (e.g., zolpidem, zopiclone, zaleplon and eszopiclone) should be administered to mitigate the risk of severe neurological events.…”
Section: Serious Versus Non-serious Reportssupporting
confidence: 93%
“…Additionally, the use of benzodiazepine compounds (as for almost half of the sample in this study) has been recently listed among predictors of delayed response to ESK-NS, arguing that the former could slow esketamine action due to the contrasting effects on the glutamatergic system [2]. However, no significant interactions or negative impact on the effectiveness of ESK-NS had been previously reported for the concomitant assumption of sedative-hypnotics/anxiolytics [41], and growing evidence shows ketamine and esketamine's anxiolytic effects in both unipolar and bipolar TRD, with a positive impact of anxious symptoms on response to ESK-NS [2]. Here, we detected significant levels of anxiety at baseline and their rapid improvement seems in line with most recent findings.…”
Section: Discussionmentioning
confidence: 68%
“…Concurrent BDZ treatment at higher doses with ketamine may dampen ketamine's antidepressant effect (Choi & Kim, 2018). BDZs exhibit a minimal effect on ketamine's rapid antidepressant effect; however, sedation was prevalent (Diekamp et al, 2021). Older Asian adults who combined BDZs with antidepressants like SSRIs and tricyclic antidepressants suffered from BDZ side effects (Zhong et al, 2019).…”
Section: Psychotropic Drugs and Neurogenesismentioning
confidence: 99%